Modifying the effect of stressed spring wheat seeds on intact ones. Issue 1 (March 2021) - Levin, V; Antipkina, L; Stupin, A; Dudin, N
Abstract: Spring wheat seeds react to the effect of stress factors of various natures with a nonspecific adaptive reaction, accompanied by intense emission of stress ethylene in trace amounts during the entire time, while. On the one hand, they remain viable, and on the other hand, have mechanical, radiation-chemical and temperature damage. Damaged air-dry seeds are not able to regenerate damaged organs and tissues and, being in a state of chronic stress, permanently induce ethylene biosynthesis. The effect of stressed seeds on intact ones is achieved remotely when they are stored together in the air environment and are blocked by active aeration, air-insulating materials and a decrease in temperature. The stronger the damaging effect on seeds is caused by the stress factor, the more intense is the accumulation of stress ethylene. An increase in the duration of exposure of intact by stressed seeds is accompanied by a more pronounced physiological modifications in seedlings of intact seeds with a sequential change in time in their stimulation of the initial growth processes and a sharp deterioration in sowing qualities.